2016
DOI: 10.1002/mc.22581
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts mediated chemoresistance by a FOXO1/TGFβ1 signaling loop in esophageal squamous cell carcinoma

Abstract: Previous studies on the mechanisms underlying ESCC (esophageal squamous cell carcinoma) chemoresistance only focused on tumor cells while tumor microenvironment has been completely ignored. Our study aimed to clarify the effect of CAFs (cancer-associated fibroblasts), one major component of tumor microenvironment, on the chemoresistance of ESCC. By primary culture, two pairs of CAFs and matched NFs (normal fibroblasts) were isolated from tumor tissues of ESCC patients and matched normal esophageal epithelial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 24 publications
1
51
0
Order By: Relevance
“…In parallel, tumor cells facilitate the transformation of normal fibroblasts into CAFs, which in turn enhance the malignant ability of tumor cells (4,25). Our previous studies revealed that CAFs were involved in tumor chemoradioresponse by secretion of chemokines and cytokines (7,8). We found that the cross-talk between CAFs and tumor cells caused the expressions of CXCL1 and TGFb1 in an autocrine/paracrine signaling loop.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In parallel, tumor cells facilitate the transformation of normal fibroblasts into CAFs, which in turn enhance the malignant ability of tumor cells (4,25). Our previous studies revealed that CAFs were involved in tumor chemoradioresponse by secretion of chemokines and cytokines (7,8). We found that the cross-talk between CAFs and tumor cells caused the expressions of CXCL1 and TGFb1 in an autocrine/paracrine signaling loop.…”
Section: Discussionmentioning
confidence: 77%
“…By use of promoter prediction tool eGPMiner, FOXO1, a transcription factor downstream of the PDGFb/PDGFRb signaling pathway, was predicted to have high affinity with two regions in the DNM3OS promoter. Our previous study had confirmed the expression of FOXO1 was obviously increased at protein level in esophageal cancer cells, which were cultured in CAF CM (7). Herein, we investigated whether FOXO1 was involved in CAF-induced DNM3OS upre-gulation.…”
Section: N E G + Ir N E G S Ir N a -1 + Ir S Ir N A -1 N E G + Ir N Ementioning
confidence: 86%
See 1 more Smart Citation
“…Although great efforts have been made to resolve the clinical issue of drug resistance, the underlying mechanism remains largely unclear [69]. Nevertheless, most studies proposed CAFs to be closely associated with chemoresistance acquisition and poor clinical prognosis [70, 71]. Dysregulation of miRNAs in CAFs and exosomal miRNA transfer between cancer cells and the microenvironment is correlated to chemoresistance regulation [72].…”
Section: Introductionmentioning
confidence: 99%
“…When it progresses to carcinoma, fibroblasts differentiate into myofibroblasts (CAFs) with expression of growth factors, matrix components, and degrading proteases promoting tumor growth. 6 They protect tumor cells from chemotherapy, [7][8][9] promote tumor invasion by remodeling the ECM structure, 10,11 and affect angiogenesis etc.…”
Section: Introductionmentioning
confidence: 99%